The Effect of Nutrition Literacy on Sugar Consumption Sweetened Drinks and Body Mass Index For High School Students in Bandung - Yakobus L. Sinaga; Yosef Pandai Lolan (Jurnal EduHealth, 2022)
According to RISKESDAS in 2018, the prevalence of diabetes in Indonesia has increased significantly compared to 2013. ON the other hand, the consumption of Sugar Sweetened Beverages (SSB) and obesity are important risk factors for Diabetes Mellitus. Hence, this study determined to analyze whether nutritional literacy in adolescents has an influence towards SSB intake and Body Mass Index among the adolescents in The City of Bandung. This is a cross-sectional study with 200 respondents with a stratified random sampling technique whereby respondents are taken from eight high schools in Bandung, randomly selected. Standardized questionnaire was used to obtained necessary data and also Kara Scan was utilized to measure BMI. There was a significant relationship between nutritional literacy and SSB consumption (p=<0.05) while there was no relationship between nutritional literacy and BMI (p=>0.05). On the other hand, nutrition literacy was a significant predictor towards SSB consumption (β = 0,085; p = <0,05) but it was not a significant predictor towards BMI (β = 0,468; p = >0,05). This study emphasized the need of an intervention to improve nutritional literacy among adolescents in Bandung to reduce SSB consumption. Hence, it will reduce the risk of developing chronic diseases as well in the future